Low-Intensity Wildfire Alters Selected Soil Properties in the Tropical Shorea robusta Forest - Badri Prasad Dhungana; Vivek Thapa Chhetri; Chitra Bahadur Baniya; Sundar Prasad Sharma (International Journal of Forestry Research)
Wildfires may impact specific soil properties differently, including positive, negative, or neutral effects. However, due to the absence of uniformity in comprehending how wildfires influence soil nutrients, this research endeavors to scrutinize the particular effect of wildfire on selected soil properties in the tropical Shorea robusta forest. We analyzed 42 soil samples obtained from the topsoil of 0–10 cm comprising 21 samples from the fire-affected area and 21 from the fire-unaffected area. The physicochemical parameters of the soil including soil pH, soil organic carbon (SOC), total nitrogen (TN), available phosphorus, and available potassium were examined and compared in two sites. The impact of fire was statistically tested after comparing each variable between the two sites. Using the Mann–Whitney U test and the Pearson correlation coefficient, we analyzed the data. The results indicated that the average chemical parameters of the soil except for pH in the fire-affected area (pH = 5.43, SOC = 1.6%, TN = 0.1%, and P=246.85 kg·ha−1) were greater than those in the fire-unaffected area (pH = 5.71, SOC = 1.21%, TN = 0.09%, and P=174.21 kg·ha−1). There were statistically significant differences in the soil parameters, including pH, SOC, TN, and P, but not with K. The soil pH was reduced in the fire-affected area, with a significant positive correlation with SOC, TN, and K. Overall, the low-intensity wildfire facilitated the proliferation of soil chemical properties in the tropical S. robusta forest. Hence, low-intensity wildfire could be a suitable forest management strategy to alter soil nutrient status. Additionally, these findings can aid in enhancing forest fire management strategies for effectively managing the tropical S. robusta forest.